PENGEMBANGAN MODUL MEMELIHARA TRANSMISI BERBASIS PBL UNTUK MENINGKATKAN KEMAMPUAN ANALISIS SISWA KELAS X PROKLI TKR SMKN 2 TARAKAN - Carolina, Novita (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2014)
The research aims to develop a manual transmission module integrated with a problem based learning models to enhanching students analytical skills . This research in addition to describe the properness module also describes the properness instructional devices, properness student analytical skills instruments, instructional implemented, student activities, student achievements and student response. Module development adopt a four - D models Thiagarajan instructional development then implemented using a randomized pretest - posttest control group design and using descriptive statistical analysis. Module, instructional devices and instruments of student analytical skills developed through logical validity of experts assessment has an average score as follows : 1) the validity of the maintain transmission module has an average score of 3.6 with a very good category, 2) the validity of the instructional devices that include syllabi, lesson plans, worksheets and assesment paper have an average score of 3.6 with a very good category, 3) the validity of the student analytical skills instruments has an avarage score of 3.7 with a very good category. While results of data analysis of the instructional implemented, student activities, student achievement and students response obtained through empirical tests, as follows: 1) the properness instructional had an average score of 3.6 with a very good category, 2) the dominant student activities in the learning process is a discussion/question and answer between students and teachers or fellow students had an average score of 3.96 with a very active category, 3) student achievement after following teaching and learning activities using a module based on PBL models increased by 69.6%, 4) students response to teaching is generally considered good scientific work and will be new parts for students. Based on the results of the data analysis above, can be concluded that learning by using maintaining transmission module with PBL models can improve students analytical skills, increases the activity of the students in learning activities and completed the students achievement.